2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6317751
|View full text |Cite
|
Sign up to set email alerts
|

Towards high-efficiency GaAs thin-film solar cells grown via close space vapor transport from a solid source

Abstract: GaAs is an attractive photovoltaic material, but its widespread implementation is limited in part by the high cost of metal-organic chemical vapor deposition, which employs toxic and pyrophoric gas-phase precursors. We study close-space vapor transport, which uses solid GaAs as a source and water vapor as a transport agent as an alternative technique for depositing GaAs films. Epitaxial n-GaAs thin films were grown on n + -GaAs substrates while varying the water vapor concentration and the source/substrate tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, while O has been detected in CSVT films at a concentration ~10 16 cm -3 by SIMS [26], the midgap state has only been detected by deep-level transient spectroscopy (DLTS) when O 2 was intentionally introduced into the reactor [27]. Increasing water vapor concentrations during growth have also been correlated with degraded photoluminescence [28] [4], although in our own work with electrochemical cells J sc was only degraded at very high water concentrations (>4000 ppm) [20]. The influence of oxygen on device performance merits further study.…”
Section: Device Propertiesmentioning
confidence: 74%
See 2 more Smart Citations
“…However, while O has been detected in CSVT films at a concentration ~10 16 cm -3 by SIMS [26], the midgap state has only been detected by deep-level transient spectroscopy (DLTS) when O 2 was intentionally introduced into the reactor [27]. Increasing water vapor concentrations during growth have also been correlated with degraded photoluminescence [28] [4], although in our own work with electrochemical cells J sc was only degraded at very high water concentrations (>4000 ppm) [20]. The influence of oxygen on device performance merits further study.…”
Section: Device Propertiesmentioning
confidence: 74%
“…We have reported that the electronic properties of GaAs grown by CSVT using H 2 O transport are satisfactory for high-efficiency PV devices, and have demonstrated the first working homojunction GaAs solar cells [19][20][21][22]. Here, we report on progress towards high-efficiency CSVT GaAs solar cells.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…arsine and trimethylgallium) employed by metal-organic chemical vapor deposition (MOCVD). Close space vapor transport (CSVT) of GaAs is a plausibly scalable process, similar to commercial CdTe deposition, which uses water vapor to generate gasphase As 2 and Ga 2 O in-situ at atmospheric pressure with high (~1 µm/min) growth rates and ~95% overall transport efficiency [1] - [2].…”
Section: Introductionmentioning
confidence: 99%
“…The reactor used for growth has been described in detail in previous publications [1] - [2]. The reaction 2 GaAs + H 2 O (g) Ga 2 O (g) + As 2 (g) + H 2 (g) occurs at atmospheric pressure under an H 2 ambient at temperatures typically between 700 and 850 ˚C.…”
Section: Introductionmentioning
confidence: 99%